Digital Modeling of ZA-type Dual-lead Worm - Hu Pingguo; Ma Chaofeng; Liu Kai; Cui Yahui (Jixie chuandong)
The geometrical characteristic of ZA-type dual-lead worm is analyzed.The mathematical model involving the ZA-type dual-lead worm is built based on the characteristic of the points of the tooth surface spiral motion during the rotation of the worm.The MATLAB is adopted to calculate the mathematical model and the calculation results are imported to SolidWorks software to generate the 3 Dsolid modeling,which lay agood foundation for NC machining,finite element analysis and dynamic analysis of the ZA-type dual-lead worm.